Trigeminal Schwannoma Extending Into the Parapharyngeal Space - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Parapharyngeal space tumors are very rarely seen, and surgical approach to these tumors has not been well established. Most of these tumors are benign and originated from salivary glands and neurogenic in nature. In this case, we report a patient who has a trigeminal schwannoma extending into the deep parapharyngeal space and explain our surgical approach.
Keywords: Trigeminal schwannoma; parapharyngeal space; SKULL-BASE; TUMORS